Disruption of Nutrient Transport, Especially Glucose, in Preeclampsia Triggers Stunted Fetal Growth - Adhi Pribadi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Preeclampsia is a relatively common complication in obstetrics. The real problem currently faced is the adverse effects of preeclampsia on the mother and fetus, while the pathophysiology useful for prevention remains unclear. The clinical symptoms and complications that arise are highly variable and ultimately lead to multi-organ failure. This condition results in preeclampsia being one of the three causes of maternal death worldwide, including in Indonesia. The incidence of preeclampsia/eclampsia in various literature and studies ranges from 4to10% of pregnancies.